(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In the article, dialogic speech is considered as one of the main forms of oral communication in foreign language teaching at technical universities. Its development in the studied foreign language is one of the most important problems of modern pedagogy. The modern demand for dialogic speech - teaching students to conduct a conversation in English - is still not perfect. For this, a more reasonable methodology of teaching dialogical speech is needed, to achieve practical results as quickly as possible, with minimal time and effort, and the learning process itself will be interesting and exciting for students.